TECHNOLOGICAL POSSIBILITIES TO INDIVIDUALIZE THE ESTHETIC OF COMPLETE DENTURES - Anca Viţalariu; Diana Diaconu; Monica Tatarciuc (Romanian Dental Association for Education, 2015)
Major concern in complete edentulism therapy is the restoration of facial aesthetics in accordance with biological and biomechanical behavior of the individual and according to the patient's temperament. Therefore, it requires the development of artificial substitutes which gives the wearer the feeling of existence of his natural teeth, in the context of psycho-affective personality, preserving the patient's aesthetic characteristics.